Leading the teacher induction and mentoring program - Sweeny, Barry W. 4 0 16; 5 (Thousand Oaks, California : Corwin Press :;National Association of Secondary School Principals, 2008)
Offers advice to leaders of teacher mentoring and induction programs on how to design and implement a new program or improve an already existing one, discussing the design process, addressing the problem of making time available for effective mentoring, providing a detailed model of mentor training, and including additional tips and resources.
Includes bibliographical references and index.
Professional.
Keywords: 2 -- 0; 6; Supervision of;Training -- Teacher orientation;Mentoring in education;First year teachers;Teachers;Mentoring.;First year teachers. -- United States.;United States.;United States.;United States; 20; 2